2020
DOI: 10.1007/s10570-020-03075-z
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of cellulose fibers measured by Brillouin spectroscopy

Abstract: We investigate the potential of Brillouin Light Scattering (BLS) Microspectroscopy for fast non-invasive all-optical assessment of the mechanical properties of viscose fibers and bleached softwood pulp. Using an optimized Brillouin spectrometer, we demonstrate fast spatial mapping of the complex longitudinal modulus over extended areas ([ 100 lm). Our results reveal that while the softwood pulp has a relatively uniform moduli, the viscous fibers have significant spatial heterogeneous in the moduli. Specificall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 34 publications
2
21
0
1
Order By: Relevance
“…The force peak at 0.25 s in the time series exhibited hysteretic forces due to adhesion but was otherwise symmetric, which indicates that there were only small contributions from time depending forces (viscoelastic behaviour). This is compatible with literature data, where storage and loss modulus of cellulose fibres were investigated via Brillouin spectroscopy (Elsayad, 2020). The authors concluded that loss modulus (viscous behaviour) was much (25 times) smaller than the storage modulus (elastic behaviour).…”
Section: Estimation Of Contact Area a And Elongation DLsupporting
confidence: 90%
“…The force peak at 0.25 s in the time series exhibited hysteretic forces due to adhesion but was otherwise symmetric, which indicates that there were only small contributions from time depending forces (viscoelastic behaviour). This is compatible with literature data, where storage and loss modulus of cellulose fibres were investigated via Brillouin spectroscopy (Elsayad, 2020). The authors concluded that loss modulus (viscous behaviour) was much (25 times) smaller than the storage modulus (elastic behaviour).…”
Section: Estimation Of Contact Area a And Elongation DLsupporting
confidence: 90%
“…The marked difference in Young's modulus between cortex and cuticle in not reflected in our Brillouin results, which show that the storage modulus for cortex is larger than that of cuticle: 16.6 and 14.1 GPa, respectively. Smaller changes in Brillouin‐derived modulus than those in quasi‐static measurements and AFM‐derived Young's modulus have already been reported for other materials, for example collagen fibres [38], cellulose fibres [29] and gelatin hydrogels [39], and attributed to different spatio‐temporal scales and different types of modulus probed by these techniques.…”
Section: Discussionmentioning
confidence: 83%
“…In our work on wool, which—similarly to hair—is mainly composed of the structural protein keratin, some of which are stabilized by disulphide bonds, we have observed a peak at 19 GHz measured at 532 nm for 180° scattering angle and in the transverse direction (radial orientation of q ) to the fibre axis [28]. A recent study by Elsayad et al has investigated the mechanical properties of cellulose fibres in light of their anisotropy and the difference between the longitudinal modulus along the fibre axis and that perpendicular to it [29]. In the present study, high‐contrast Brillouin microscopy was employed to map the viscoelastic properties of human hair and to investigate the effect of bleaching.…”
Section: Introductionmentioning
confidence: 99%
“…By its definition, the BLT does not depend on the sample refractive index and density and thus provides a simple approach to determine whether mechanical properties are the main contributor to observed changes in the Brillouin spectrum and their spatial maps. A similar approach has been recently used to study bulk mechanical properties and their differences in tumor spheroids 24 and cellulose fibers 30 , but has not yet been used for spatial mapping. From a mechanical viewpoint, the loss tangent can be understood as the relative contribution of effective viscosity to longitudinal modulus within the probed, micrometer-scale region of the sample.…”
Section: Quantifying Cell and Tissue Materials Properties With Brilloumentioning
confidence: 99%